A general perspective regarding the relation between institutional efficiency and (economic) development in Eastern Europe - Ramona Țigănașu; Sorin Mazilu (CES Working Papers, 2019)
Informal institutions such as culture, trust, social relations, norms or values have a strong effect on countries' development patterns, their role being enhanced in those states where formal institutions are poorly regulated. Therefore, in order to foster economic development, institutional change remains one of the core issues, and differs depending on the levels of social analysis. The current paper aims at outlining a general perspective regarding the relation between institutional efficiency and economic development within the European Union, with a specific focus on the Eastern member states of the European Union. These new members have similar development patterns and structural challenges, considering their shared communist past and inheritance which have left strong imprints on Eastern European societies and welfare. Overall, the paper argues that institutional efficiency is closely linked to the countries' levels of prosperity, and consequently, to the manner in which their governments focus on development policies, especially in those countries that are economically and spatially more peripheral.
Keywords: 330; social capital; formal and informal institutions; economic freedom